PENERAPAN FEM UNTUK MENENTUKAN MATERIAL KOMPONEN PROPULSI ROKET RKX-10C16 - Samosir, Ganda (BRIN Publishing, 2010)
One of the most important rocket propulsion components is nozzle where the thermal energy is converted to kinetics and finally became the mechanics energy in the form of thrust. During the combustion process of the propellant, the nozzle will be influenced by some constraints, namely the pressure and the thermal. The nozzles material chosen, must than be strength enough to minimize those constraints, but still, the nozzle must be weight enough. The Finite Element Method (FEM) used to analyze the nozzles structure strength must be applied to those constraints separately. The result is then compared to the technical specification of the nozzle material chosen. From the static test of the rocket 100 mm clases, it is known that the operating pressure is 46 kg/cm2= 4,51 MPa and 3000ºC of temperature but about 90 % are absorbed by the tube liners (inhibitor). If the calculated safety factor minimum, min F S ≥ 1, the selected material then meets the requirement. Basically, the rocket nozzle consist of two different materials, the outer side is made from the metal (steel), the inner one is from the graphite, but the calculation in this paper was made to the metal part only. After being well analyzed, we arrive then to the conclusion that the metal part of the nozzle is made from the carbon steel S-45C.